2015
DOI: 10.4236/ojvm.2015.51002
|View full text |Cite
|
Sign up to set email alerts
|

Propolis in Dogs: Clinical Experiences and Perspectives (A Brief Review)

Abstract: In light of the scarcity of novel therapeutic agents that are effective, the pharmaceutical industry has found a newer source of therapeutic compounds in natural products and herbal medicine to address the current health problems in humans and animals. What is particularly promising about these agents is that they produce fewer side effects and are more cost effective than synthetic compounds. This means greater availability of these treatments particularly for less developed countries who can't afford expensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In this study, the experimental animals of choice were the Dogs due to several advantages including: being less expensive to maintain, cost effective to feed and they show patterns of bone accretion and peak bone mass profiles similar to those of human as well as true skeletal maturity (15).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the experimental animals of choice were the Dogs due to several advantages including: being less expensive to maintain, cost effective to feed and they show patterns of bone accretion and peak bone mass profiles similar to those of human as well as true skeletal maturity (15).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with mixed breed healthy dogs, Darweesh et al, (2014) observed that propolis was a good means of teeth storing before the reimplantation, which increased the success rate of the procedure. It is worth noting that these compounds inhibit the connection of bacteria to the tooth surface, so that their antibacterial activity would not induce bacterial resistance, which emphasizes their potential as an oral antiseptic (Ilewicz et al, 1979;Betancourt et al, 2015).…”
Section: Natural Products As Adjuncts Of Oral Hygienementioning
confidence: 99%
“…In addition to veterinary follow-up, dog owners can make use of various products for dogs' oral care, such as dentifrices for brushing, mouthwash and oral chewable products that promote mechanical cleaning or have active components with antimicrobial activity (Lima et al, 2004;Gallagher, 2013;Moshkelani et al, 2014). Development, v. 9, n. 10, e369108413, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8413 5 With time and observation, humans were able to identify the therapeutic effects of natural resources available for treatment and prevention of pathological states (Betancourt et al, 2015). Thus, the presence of natural products in dentistry is not a novelty once that compounds such as agar-agar, citric acid, eugenol and thymol have been part of the clinical routine for some time.…”
Section: Introductionmentioning
confidence: 99%
“…(Leguminose) resin exhibits important biological Research, Society and Development, v. 9, n. 11, e70391110531, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10531 properties, such as the ability to eliminate free radicals and inhibit tumor cell growth, constituting an excellent source of antioxidant and antitumor natural agents, in addition to antimicrobial, antifungal, and antiparasitic activities, including leishmanicidal activity (Frozza et al, 2012;do Nascimento et al, 2016;Li et al, 2017;de Silva, 2017;Silva et al, 2019) In dogs, the beneficial effect of propolis was studied for different purposes. Clinical experiences were related to antimycotic, Cushing syndrome, ophthalmic, and paradental use; experimental studies in vitro or in vivo (rats or mice) in canine neoplastic cells, such as immunostimulants, bactericides, and antiparasitic (Betancourt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%